Impact of gut microbiota on severity of obsessive-compulsive disorder (OCD) - a short review - Kacper Niewęgłowski; Natalia Wilczek; Michał Rycharski; Julita Niewęgłowska (Kazimierz Wielki University, 2022)
Introduction and purpose  Obsessive-compulsive disorder (OCD) has an unclear etiology. Genetic and environmental factors dominate among the etiologic factors. The disorder is characterized by the presence of obsessions (repetitive and persistent thoughts, images, impulses or urges) and compulsions (rituals; repetitive behaviours or mental acts that the individual feels driven to perform in response to an obsession). This disorder has less than 4% of the population. Treatment is a long and difficult process, and the best results are with SSRIs (e.g., fluoxetine) and cognitive behavioral therapy (CBT). The aim of the study was to review articles linking gut microbiota and obsessive-compulsive disorder issues.    A brief description of the state of knowledge  The gut microbiota-gut-brain axis perhaps has an impact on the etiology of psychiatric diseases. Its existence has been well researched in animals. Researches suggest that there possibly may be changes in the composition of the gut microbiota in people with obsessive-compulsive disorder. Quantitative and qualitative changes in the gut microbiota composition may worsen the patient's condition. The use of probiotics may help improve the patient's condition and reduce symptoms of the disorder.    Summary (conclusions)  More research is needed to explore the potential impact of the gut microbiota on obsessive-compulsive disorder. This could perhaps lead to future applications of probiotics, e.g., in the adjunctive treatment of obsessive-compulsive disorder.